Estimating pentose phosphate pathway activity from the analysis of hepatic glycogen 13 C-isotopomers derived from [U-13 C]fructose and [U-13 C]glucose - Belew, Getachew D. (2020)
The pentose phosphate pathway (PPP) is an important component of hepatic intermediary metabolism. Jin et al developed an elegant 13 C-NMR method for measuring hepatic PPP flux by quantifying the distribution of glucose 13 C-isotopomers formed from [U-13 C]glycerol. We demonstrate that this approach can be extended to exogenous [U-13 C]fructose and [U-13 C]glucose precursors by 13 C-NMR analysis of glycogen.